Adenovirus Remodeling of the Host Proteome and Host Factors Associated with Viral Genomes - Joseph M. Dybas (American Society for Microbiology, 2021)
Viral infections induce myriad changes to the host cell proteome. As viruses harness cellular processes and counteract host defenses, they impact abundance, posttranslational modifications, interactions, or localization of cellular proteins.